Rehabilitation Following Surgery for Glenohumeral Instability. Issue 3 (September 2017) - Johnson, Michael
Abstract : Shoulder dislocation and subsequent instability is a common problem in young athletes. Though it is not uncommon to attempt nonoperative rehabilitation in the early going, reinjury rates are high, particularly with contact sport athletes. As a result, many athletes will undergo a primary repair of one, or multiple, glenohumeral ligaments that make up the anterior shoulder capsule. This paper presents phases of rehabilitation from the preoperative stage up to returning to play. Criteria for phase progression are included, along with examples of common exercises and themes for each phase that allow the physical therapist to consider when working with patients who have had this type of shoulder surgery, allowing them to return to full function with low risk of reinjury.